The effect of chiral end groups on the assembly of supramolecular polyurethanes. Issue 31 (22nd July 2021) - Hermida-Merino, Daniel; Hart, Lewis R.; Harris, Peter J.; Slark, Andrew T.; Hamley, Ian W.; Hayes, Wayne
Abstract : We describe the generation of supramolecular polyurethanes and the positive effect that chirality has upon the physical properties of these materials. Abstract : The ability to influence the physical properties of supramolecular polymers has been the subject of numerous synthetic studies in recent years. Tuning properties by adjustment of the polymer composition to modify the degree of phase separation of polar (hard) and apolar (soft) segments in addition to variation of the capability of the polar end groups to self-assemble efficiently via non-covalent interactions (such as hydrogen bonding, aromatic π–π stacking or metal–ligand binding) has yielded materials with attractive thermo-reversible characteristics. Previously, we have studied supramolecular polyurethanes (SPUs) to understand in more detail the interplay and importance of phase separation and the binding affinity of the polar end group on the physical properties of these interesting thermo-responsive materials. In this paper, we report the positive effect that chirality has upon the self-assembly and physical properties of SPUs. The synthesis of a series of novel SPUs that feature chiral polar end-groups is described in addition to how these chiral moieties improve the order of the relatively weak hydrogen bonding units in this type of supramolecular polymer. The introduction of chiral moieties in the polymer end group induces cooperative arrangements of the components of the hard segments (urethane, urea and aromatic units), leading to SPUs with increased ordered and stronger supramolecular hard segments. The supramolecular interactions of the chiral hard segments were first evaluated by CD and FTIR spectroscopies. In addition, the thermo-responsive nano-segregated structure formed by the columnar aggregates of the SPUs generated was probed by variable temperature CD and FTIR spectroscopies in addition to simultaneous SAXS/WAXS analysis. These studies confirmed the microphase separation morphology also revealed by AFM analysis. Additionally, rheological analysis of the chiral SPUs highlighted the enhancement of the rubbery plateau of chiral SPUs derivatives in comparison to analogous racemic SPUs as a result of the chiral self-assembly motifs. Finally, to explore the mechanical properties of the afforded polymers, electrospinning experiments were undertaken which revealed that defined microfibers were formed at lower concentrations in the case of the homochiral SPUs ( ca . 15%) when compared to the racemic analogue, thus confirming the improvement in the supramolecular interactions afforded by the chiral groups.